EVALUATION OF THE SHORT-TERM AND DELAYED RISKS OF THE ABNORMAL SUMMER 2010 HEAT IMPACT IN SEVERAL DISTRICTS OF NIZHNY NOVGOROD OBLAST, CLOSE TO WILDFIRES, ON THE MORBIDITY AND MORTALITY OF INHABITANTS - M. D. Smirnova; Yu. V. Badin; O. Yu. Badina; A. R. Vaisberg; D. S. Polyakov; E. V. Shcherbinina; F. T. Ageev; F. T. Fomin (Кардиоваскулярная терапия и профилактика, 2015)
The influence of abnormal summer heat (AH) in the year 2010 on morbidity and mortality in Russian Federation regions is not studied good enough. Nizhny Novgorod Oblast was one of the most involved and harmed.Aim. Retrospective assessment of short- and long-term influence of AH and fires of the summer 2010 on the course of cardiovascular diseases living in several districts of Nizhny Novgorod Oblast.Material and methods. Totally, 779 inhabitants of Vyksunsky district of Nizhny Novgorod Oblast were included. The analysis of outpatient charts was done (data 2010-2014), questionnaires were used.Results. The period of AH (PAH) was followed by the increase of mortality from external causes (p<0,01) comparing to the summer 2011. Mortality in September-December 2010, cardiovascular as from other reasons, was significantly lower that during the same period in 2011 (p<0,05). Combination endpoints (CEP) were more common for PAH comparing to the same period of 2011 and 2012, and September-December 2010. CEP were lower in September-December 2010 than in 2012. Quantity of cardiovascular complications (CVC) in PAH did not differ from average for this period of the year, and was lower than in fall-winter period of 2011 and 2012. More CVC in PAH developed in cardiovascular patients, with arterial hypertension, post infarction cardio sclerosis, cerebrovascular disease. An independent risk factor for CEP in PAH were age, for CVC — functional class of chronic heart failure. Predictors of life quality worsening in PAH: male sex, smoking, living close to roads and on upper floors, higher education. With better life quality in PAH were associated the presence of climat-control of even ventilator, higher body mass index and taking of angiotensin-converting enzyme inhibitor.Conclusion. AH led to the increase of general mortality but did not led significantly to increase of cardiovascular morbidity and CV complications. With the highest risk of complications during the heat were associated: existence of arterial hypertension, post infarction cardio sclerosis, chronic heart failure, cerebrovascular disease, older age.